Women's Imprisonment in Britain and Ireland - Quinlan, Christina (The prison journal, 2022)
This research, utilizing a case study design, focused on prison operations in women's prisons and compared those across each of the four jurisdictions of England and Wales, Scotland, Northern Ireland, and the Republic of Ireland. The numbers of women in prison, the crimes for which they are imprisoned, and their sentences are considered, along with women's prison policy initiatives in each jurisdiction. The differences between these policies and the realities of women's experiences in prison are highlighted.